Cyclic Stretch Alters Vascular Reactivity of Mouse Aortic Segments - Leloup, Arthur; De Moudt, Sofie; Van Hove, Cor; Fransen, Paul (Frontiers in Physiology, 2017)
Large, elastic arteries buffer the pressure wave originating in the left ventricle and are constantly exposed to higher amplitudes of cyclic stretch (10%) than muscular arteries (2%). As a crucial factor for endothelial and smooth muscle cell function, cyclic stretch has, however, never been studied in ex vivo aortic segments of mice. To investigate the effects of cyclic stretch on vaso-reactivity of mouse aortic segments, we used the Rodent Oscillatory Tension Set-up to study Arterial Compliance (ROTSAC). The aortic segments were clamped at frequencies of 6–600 bpm between two variable preloads, thereby mimicking dilation as upon left ventricular systole and recoiling as during diastole. The preloads corresponding to different transmural pressures were chosen to correspond to a low, normal or high amplitude of cyclic stretch. At different time intervals, cyclic stretch was interrupted, the segments were afterloaded and isometric contractions by α1-adrenergic stimulation with 2 μM phenylephrine in the absence and presence of 300 μM L-NAME (eNOS inhibitor) and/or 35 μM diltiazem (blocker of voltage-gated Ca2+ channels) were measured. As compared with static or cyclic stretch at low amplitude (<10 mN) or low frequency (0.1 Hz), cyclic stretch at physiological amplitude (>10 mN) and frequency (1–10 Hz) caused better ex vivo conservation of basal NO release with time after mounting. The relaxation of PE-precontracted segments by addition of ACh to stimulate NO release was unaffected by cyclic stretch. In the absence of basal NO release (hence, presence of L-NAME), physiological in comparison with aberrant cyclic stretch decreased the baseline tension, attenuated the phasic contraction by phenylephrine in the absence of extracellular Ca2+ and shifted the smaller tonic contraction more from a voltage-gated Ca2+ channel-mediated to a non-selective cation channel-mediated. Data highlight the need of sufficient mechanical activation of endothelial and vascular smooth muscle cells to maintain basal NO release and low intracellular Ca2+ in the smooth muscle cells in large arteries. Both phenomena may play a vital role in maintaining the high compliance of large arteries.